ANALISIS KEBUTUHAN INSTRUMEN PENILAIAN KEMAMPUAN DASAR MEMBACA AKSARA JAWA PADA SISWA KELAS VIII - Mira Yahdhi Mas’ulla; Suriswo; Khusnul Khotimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the needs in developing an assessment instrument for basic Javanese script reading skills among eighth-grade junior high school students. A preliminary study conducted in three junior high schools in Talang Subdistrict revealed that approximately 80% of students face difficulties in reading Javanese script. These difficulties are mainly observed in distinguishing the shapes of characters, understanding the use of sandhangan (diacritics), character pairs, and punctuation marks (pada). In addition, Javanese numerals are also an aspect that students have not fully mastered. The assessments conducted by teachers so far tend to be informal and do not utilize standardized instruments, resulting in less objective and unstandardized evaluations of students’ abilities. This research employs the Research and Development (R&D) method using the ADDIE model, with the current focus on the needs analysis stage. The analysis results indicate that both teachers and students require a valid and reliable assessment instrument, preferably in an easy-to-understand multiple-choice format. Developing such an instrument is crucial to enhance the effectiveness of Javanese script learning and support cultural preservation through education.